Schools of the Commission of National Education’s Greater Poland Department - Żołądź-Strzelczyk, Dorota (1955– ); Nowicki, Michał; Ratajczak, Krzysztof; Gulczyńska, Justyna (Instytut Historii Nauki im. Ludwika i Aleksandra Birkenmajerów Polskiej Akademii Nauk, 2018)
The Commission of National Education created a comprehensive school network, including the Greater Poland Department, consisting of department and subdepartment schools along with loosely connected with them parochial schools, which in its entirety remained under the authority of the Crown Main School. This article presents the history of the Greater Poland Department from the time of the Commission of National Education’s establishment in 1773 until the Commission terminated its operations in this region amid the Partitions of Poland in 1793. This study explores the department school in Poznań, the subdepartment schools in Kalisz, Wschowa, Trzemeszno, Toruń and Międzyrzecz as well as the parochial schools.
Keywords: Commission of National Education; Greater Poland Department; Old Polish education system